(untitled) (KULT_online, 2022)
Ballet in the Cold War: A Soviet-American Exchange explores the issue of Cold War diplomacy through an investigation of the ballet tours of the Bolshoi Theater and the New York City Ballet in the early 1960s. Anne Searcy highlights the crossroads of dance, music, politics, and their perception. She has successfully applied the concept of ‘transliteration’ to the specific context of inter-bloc cultural exchange and investigates the topic from a new angle by incorporating unexplored sources.